2007
DOI: 10.1200/jco.2006.08.7916
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization of Liver Metastases From Colorectal Cancer Using Yttrium-90 Microspheres With Concomitant Systemic Oxaliplatin, Fluorouracil, and Leucovorin Chemotherapy

Abstract: The maximum-tolerated dose was 60 mg/m2 of oxaliplatin for the first three cycles, with full FOLFOX4 doses thereafter. This chemoradiation regime merits evaluation in phase II-III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
185
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(197 citation statements)
references
References 32 publications
4
185
0
8
Order By: Relevance
“…These rates compare favorably with other reported cohorts who received Y90 treatment. [19][20][21] Significant adverse events to Y90 therapy usually are GI in nature. This is most likely because of the inadvertent deposition of microspheres into the GI tract through unrecognized collateral vessels, leading to ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…These rates compare favorably with other reported cohorts who received Y90 treatment. [19][20][21] Significant adverse events to Y90 therapy usually are GI in nature. This is most likely because of the inadvertent deposition of microspheres into the GI tract through unrecognized collateral vessels, leading to ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…Basierend auf den Daten einer Phase-I-Studie wurde die Kombination von SIRT mit einer FOLFOX-Chemotherapie in 3 randomisierten Multicenterstudien (SIRFLOX, FOXFIRE und FOXFIRE global) untersucht [1205].…”
Section: Hintergrundunclassified
“…A number of large scale studies using FOLFOX or its variants have consistently yielded RECIST response rates of 50-60%, progression-free survival of 8-9 months and median survival of 16-18 months [25]. Sharma et al [26] reported promising results from a Phase I-II trial of FOLFOX chemotherapy in combination with RE for patients with unresectable colorectal liver metastases in the first line setting. Twenty patients were treated with oxaliplatin at escalating doses of 30-85mg/m 2 and full dose 5LV/5FU for Cycle 1-3 and full dose FOLFOX 4 for cycles 4-12.…”
Section: Optimal Combinations Of Systemic Chemotherapy With Re In Metmentioning
confidence: 99%
“…The practice at our institution is to offer oxaliplatin and 5-FU chemotherapy (in the dosing regime shown to be safe in reference [26]) with RE as second line or subsequent line therapy for patients with liver-dominant or liver-only metastases from colorectal cancer, regardless of their previous chemotherapy history. In patients who have experienced unacceptable toxicity with oxaliplatin (e.g.…”
Section: Guidelines For Combining Re With Systemic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation